Child mortality in England compared with Sweden: a birth cohort study. Issue 10134 (19th May 2018) - Zylbersztejn, Ania; Gilbert, Ruth; Hjern, Anders; Wijlaars, Linda; Hardelid, Pia
Summary: Background: Child mortality is almost twice as high in England compared with Sweden. We aimed to establish the extent to which adverse birth characteristics and socioeconomic factors explain this difference. Methods: We developed nationally representative cohorts of singleton livebirths between Jan 1, 2003, and Dec 31, 2012, using the Hospital Episode Statistics in England, and the Swedish Medical Birth Register in Sweden, with longitudinal follow-up from linked hospital admissions and mortality records. We analysed mortality as the outcome, based on deaths from any cause at age 2–27 days, 28–364 days, and 1–4 years. We fitted Cox proportional hazard regression models to estimate the hazard ratios (HRs) for England compared with Sweden in all three age groups. The models were adjusted for birth characteristics (gestational age, birthweight, sex, and congenital anomalies), and for socioeconomic factors (maternal age and socioeconomic status). Findings: The English cohort comprised 3 932 886 births and 11 392 deaths and the Swedish cohort comprised 1 013 360 births and 1927 deaths. The unadjusted HRs for England compared with Sweden were 1·66 (95% CI 1·53–1·81) at 2–27 days, 1·59 (1·47–1·71) at 28–364 days, and 1·27 (1·15–1·40) at 1–4 years. At 2–27 days, 77% of the excess risk of death in England was explained by birth characteristics and a further 3% by socioeconomic factors. At 28–364 days, 68% of the excess risk of death in England was explained by birth characteristics and a further 11% by socioeconomic factors. At 1–4 years, the adjusted HR did not indicate a significant difference between countries. Interpretation: Excess child mortality in England compared with Sweden was largely explained by the unfavourable distribution of birth characteristics in England. Socioeconomic factors contributed to these differences through associations with adverse birth characteristics and increased mortality after 1 month of age. Policies to reduce child mortality in England could have most impact by reducing adverse birth characteristics through improving the health of women before and during pregnancy and reducing socioeconomic disadvantage. Funding: The Farr Institute of Health Informatics Research (through the Medical Research Council, Arthritis Research UK, British Heart Foundation, Cancer Research UK, Chief Scientist Office, Economic and Social Research Council, Engineering and Physical Sciences Research Council, National Institute for Health Research, National Institute for Social Care and Health Research, and the Wellcome Trust).